Texturing of polycrystalline photovoltaic materials using vertically aligned carbon nanotube arrays. (7th December 2012) - Flicker, Jack; Ready, W. Jud
ABSTRACT In order to demonstrate that three‐dimensional carbon nanotube‐based photovoltaic devices show an increase in power output over similar planar cells, we have produced cells with texturing through the use of vertically aligned carbon nanotube arrays and cells without this texturing. The output power of these cells at varying incident angles of light was measured. The textured cells show an increase in the normalized power output compared with similar planar cells when the solar flux is at off‐normal angles. The power output versus incident angle curve takes an inverted C‐type curve as predicted by the theory developed previously, with very good agreement between experimental results and theoretical predictions. Copyright © 2012 John Wiley & Sons, Ltd.